WEBVTT
00:00:02.570 --> 00:00:09.750
Find the multiplicative inverse of root six plus root seven expressing your answer in its simplest form.
00:00:11.290 --> 00:00:14.790
So first of all, we need to know a little bit about the multiplicative inverse.
00:00:15.550 --> 00:00:21.260
But what we can say is, the product of a number and its multiplicative inverse is one.
00:00:22.740 --> 00:00:29.820
So therefore, we can also say that the multiplicative inverse of a number must be its reciprocal.
00:00:31.330 --> 00:00:41.950
So therefore, the MI, this is what I’m gonna call the multiplicative inverse, of root six plus root seven must be equal to one over root six plus root seven.
00:00:43.570 --> 00:00:49.830
And this is because one over root six plus root seven is the reciprocal of root six plus root seven.
00:00:50.390 --> 00:00:56.890
Also, if we multiplied them together, we’d get root six plus root seven over root six plus root seven.
00:00:57.230 --> 00:01:00.160
Which would give us our answer of one, which is what we’d be looking for.
00:01:01.980 --> 00:01:05.600
So we’ve now found the MI of root six plus root seven.
00:01:05.710 --> 00:01:08.100
So that’s the first part of the question complete.
00:01:08.720 --> 00:01:09.630
But have we finished?
00:01:10.820 --> 00:01:14.530
Well, no because we also need to express the answer in its simplest form.
00:01:15.550 --> 00:01:22.760
And to enable us to do that, what we need to do is rationalize the denominator because we don’t want surds on the bottom.
00:01:24.650 --> 00:01:37.000
And in order to rationalize the denominator, what we need to do is we need to multiply the fraction, so our one over root six plus root seven, by the conjugate of the denominator.
00:01:38.460 --> 00:01:43.950
And the conjugate of an expression is where we change the sign in the middle of the two terms.
00:01:44.170 --> 00:01:49.800
For example, if we had 𝑥 squared minus three, the conjugate would be 𝑥 squared plus three.
00:01:51.090 --> 00:01:55.480
So therefore, in our problem, we’ve got root six plus root seven.
00:01:55.530 --> 00:01:58.630
So therefore, the conjugate is root six minus root seven.
00:02:00.080 --> 00:02:07.700
So therefore, we’re gonna have one over root six plus root seven multiplied by root six minus root seven over root six minus root seven.
00:02:08.280 --> 00:02:11.770
So we’re actually gonna be multiplying both the numerator and the denominator.
00:02:12.060 --> 00:02:15.660
The reason we’re doing that is because whatever you do to one, you must do to the other.
00:02:17.250 --> 00:02:26.520
So we’re just gonna have root six minus root seven as our numerator because one multiplied by root six minus root seven is just root six minus root seven.
00:02:27.710 --> 00:02:32.680
Now to get the expression for the denominator, what we need to do is expand the parentheses.
00:02:32.680 --> 00:02:40.790
If we multiply root six plus root seven by root six minus root seven, so therefore, for our first term, we’re gonna get six.
00:02:40.820 --> 00:02:43.160
And we get that because we use one of our surd rules.
00:02:43.510 --> 00:02:48.350
And that’s if we have root 𝑎 multiplied by root 𝑎, the result is just 𝑎.
00:02:48.930 --> 00:02:55.160
And that’s because if we did root six, for instance, multiplied by root six, this will give us root 36.
00:02:55.510 --> 00:02:59.690
Or the square root of 36 is six, so that’s why we get that result.
00:03:01.190 --> 00:03:04.530
And then we have root six multiplied by negative root seven.
00:03:04.530 --> 00:03:07.070
So it gonna give us negative root six root seven.
00:03:08.250 --> 00:03:10.640
And then we’re gonna have plus root six root seven.
00:03:10.750 --> 00:03:14.900
And that’s because we’ve got positive root seven multiplied by positive root six.
00:03:16.910 --> 00:03:19.410
And then, finally, we’ve got minus seven.
00:03:19.560 --> 00:03:23.600
And we got that because we had positive root seven multiplied by negative root seven.
00:03:24.040 --> 00:03:26.650
So again, root seven multiplied by root seven gives us seven.
00:03:26.950 --> 00:03:32.140
And we get a negative because we multiplied a positive and a negative, which gives a negative result.
00:03:33.660 --> 00:03:39.990
Then, we can cancel out root six root seven because we’ve got negative root six root seven plus root six root seven, which would just be zero.
00:03:41.440 --> 00:03:45.290
So then we’re left with six minus seven, which just gives us negative one.
00:03:46.570 --> 00:03:52.860
And this is why this is called rationalizing the denominator because as you can see, there are now no surds on the denominator.
00:03:53.090 --> 00:03:54.570
So we’ve just got negative one.
00:03:55.980 --> 00:03:59.060
So now we have root six minus root seven over negative one.
00:04:00.750 --> 00:04:08.190
So therefore, as we’re dividing by negative one, all we need to do is change the signs of both terms in our expression on the numerator.
00:04:08.610 --> 00:04:17.450
So, we could say that the multiplicative inverse of root six plus root seven, expressed in its simplest form, is root seven minus root six.